2015
DOI: 10.3390/f6082678
|View full text |Cite
|
Sign up to set email alerts
|

Response of Boreal Jack Pine (Pinus banksiana Lamb.) Stands to a Gradient of Commercial Thinning Intensities, with and without N Fertilization

Abstract: This study examines tree and stand response to a gradient of commercial thinning intensities and nitrogen fertilization (200 kg N ha−1) in nine jack pine (Pinus banksiana) stands of Eastern Canada over a period of 14 years. Thinning intensity ranged from 0% basal area removal in control plots to 64% in thinned plots. Tree diameter increment, absolute and relative volume increment and mean volume increased with thinning intensity and were higher in fertilized plots. Individual tree response depended on tree dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…It was found that, immediately after thinning, there was a decrease in stand volume growth, typically lasting approximately 10 years, levelling off after this period [50]. In addition, the remaining trees had a greater volume increment if thinning was more intense [44,48,51].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that, immediately after thinning, there was a decrease in stand volume growth, typically lasting approximately 10 years, levelling off after this period [50]. In addition, the remaining trees had a greater volume increment if thinning was more intense [44,48,51].…”
Section: Discussionmentioning
confidence: 99%
“…High intensity fires can hinder regeneration [11], but medium intensity fires increase tree diversity and delay replacement by other species [12]. Pre-commercial thinning and fertilization improves tree growth [13,14], with the largest effect being observed for young trees [15] and represent potentially viable silvicultural investments [16]. Considering the ecological and economic importance of this species in the boreal forest, there is a need for improved knowledge on growth, yield and mortality of jack pine.…”
Section: Introductionmentioning
confidence: 99%
“…Crop-species responses to silvicultural treatments vary, however, depending on key functional traits such as shadetolerance or nutrient requirements (Périé and Munson 2000, Wagner and Robinson 2006, Kranabetter et al 2017. For example, we recently observed that fast-growing, light-demanding jack pine (Pinus banksiana Lamb.)…”
Section: Introductionmentioning
confidence: 99%
“…BSP) responded linearly to this variable (Thiffault et al 2012b). Silvicultural treatments can also interact with each other, leading to multiplicative rather than additive responses of planted trees; for example, Nilsson and Örlander (2003) reported that fertilization significantly increased Norway spruce growth in the short-term when combined with herbicide application, but fertilization effects were not significant when competing vegetation was left untouched. Interactions between planted species and silvicultural treatments, and among silvicultural treatments, make it difficult to predict mid-and long-term impacts of reforestation strategies on stand productivity (Mason 1992), and there is thus a need to acquire and analyse long-term empirical data from silvicultural trials to inform the management decisions required for sustainable production of ecosystem services, including wood supply.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation